DIAGNOSIS OF SENSE OF JUSTICE AS CONDITIONS OF MORAL DEVELOPMENT OF THE MODERN TEACHER (Pedagogy of Higher and Secondary Education, 2009)
This article is a study of the concepts of "fairness" and "injustice" to the teachers of schools, the study also highlighted forms of injustice, which are most often found in educational practice.